Frames of war : when is life grievable? - Butler, Judith (Radical Thinkers, 2016)
In this urgent response to violence, racism and increasingly aggressive methods of coercion, Judith Butler explores the media’s portrayal of armed conflict, a process integral to how the West prosecutes its wars. In doing so, she calls for a reconceptualization of the Left, one united in opposition and resistance to the illegitimate and arbitrary effects of interventionist military action. -- Présentation de l'éditeur.